The future of AI in government services and global risks: insights from design fictions - Pedro Vitor Marques Nascimento; Paloma Beatriz Belchior de Siqueira; Nathalia Chrispim; Ramon Miranda Chaves; Carlos Eduardo Barbosa; Jano Moreira de Souza (European Journal of Futures Research)
Abstract The evolution of government services in the context of Artificial Intelligence (AI) and its long-term implications are relevant topics impacting society. Developments in this area are surrounded by controversies about what is technically possible, what is feasible in terms of implementation, and what is desirable. In addition, AI’s ambiguous capacity to mitigate and accentuate global risks is remarkable. This research explores AI’s long-term implications through a literature-based design fiction approach, constructing speculative scenarios to examine the potential consequences of AI adoption in governance. The findings highlight three critical dilemmas: (1) AI’s dual role in enhancing efficiency while exacerbating algorithmic bias and surveillance concerns; (2) the potential displacement of human roles in public services, raising questions about accountability and transparency; and (3) the ethical trade-offs in AI-driven decision-making, particularly in law enforcement, healthcare, and education. These scenarios provide insights into the governance challenges AI may introduce, emphasizing the need for ethical guidelines, policy frameworks, and stakeholder engagement. By leveraging speculative narratives, this work contributes to Futures Research on AI in the public sector by offering a creative yet critical lens through which to explore its socio-technical impacts and global risks. These fictional stories will play a fundamental role in stimulating broader dialogues, exploring how AI may influence and redesign the roles played by professionals in government services and the citizens who use them.